Patients with transcatheter valve procedures admitted to contemporary cardiac intensive care units: insights from the CCCTN registry. (3rd May 2023) - Bhatt, A; Berg, D; Palazzolo, M; Bohula, E; Morrow, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Transcatheter cardiac valve procedures, including transcatheter aortic valve replacement (TAVR) and transcatheter edge-to-edge repair (TEER), have increased in the recent years. Peri-procedural management strategies, including whether there is a need for routine admission to cardiac intensive care units (CICUs), are not well defined. Purpose: We aimed to describe the epidemiology of patients with transcatheter cardiac valve procedures admitted to contemporary CICUs. Methods: We identified patients who underwent transcatheter cardiac valve procedures (TAVR or TEER) from CICUs in North America from 2017 to 2021 using data from the CCCTN (Critical Care Cardiology Trials Network) Registry. We assessed patient characteristics and the reason for triage to a CICU among those admitted for TAVR or TEER. Among patients admitted for TAVR or TEER, we further compared resource utilization and outcomes between patients (1) with an admission or CICU indication of post-procedural monitoring alone versus (2) admissions following TAVR or TEER for other reasons. Results: Of 17, 852 CICU admissions, 641 (3.6%) had a TAVR/TEER leading to or during their CICU stay. Compared with patients without a TAVR/TEER during CICU stay, patients with the procedure were older (median [IQR]: 80 [74-85] vs. 66 (55-75) years) and a history of coronary artery disease (54% vs. 36%, P<0.01). Monitoring alone, without another CICU indication at the time of admission, was the most frequent admission indication in patients with TAVR/TEER (n= 474, 74%). Patients admitted with TAVR or TEER for monitoring alone had low rates of any shock (2%) and mechanical ventilation (3%) and low SOFA scores (2 [1-4]); Figure). In contrast, patients with TAVR/TEER admitted for other indications had higher rates of shock (26%) and mechanical ventilation (25%) and higher SOFA scores (4 [3-7]). There were 0 cases of mechanical circulatory support (MCS) use in patients admitted for monitoring only. CICU (0.2% vs. 4.2%) and in-hospital (1.5% vs. 9.0%) mortality was multifold lower in patients with TAVR or TEER admitted for monitoring alone compared to patients with TAVR or TEER with an admission indication beyond monitoring. Conclusions: In contemporary North American CICUs, nearly 3 of 4 admissions of patients with TAVR or TEER are for procedural monitoring alone. Need for advanced CICU therapies and mortality rates were low among patients admitted to the CICU for monitoring alone following TAVR or TEER. Given expected growth of these procedures over time, these observations highlight potential opportunities to redirect triage of the majority of patients following TAVR or TEER to less costly hospital units.